Ṭibāq Styles in the Book ‘Umdah Al- Ahkām Min Kalāmi Khair Al-An’ām (the Balagah Study) - Abdul Azis; Yusroh Yusroh (Universitas Ahmad Dahlan, 2021)
This study aims to determine the ṭibāq language style used in the book ʻUmdah al-Ahkām min Kalām Khair al-Anām and to analyze the types and forms of ṭibāq language style contained in it. The method used in this study is a qualitative method with observation and note-taking techniques in data collection. In analyzing the data used the method of agih with the basic technique of BUL (For Direct Elements). The data presentation used a qualitative descriptive method. The results of this study indicate that in the book ʻUmdah al-Ahkām min Kalām Khair al-Anām there are 63 data with 61 hadith containing ṭibāq, of which 48 ṭibāq ījāb and 15 ṭibāq salab. Ṭibāq ījāb in the form of fiʻil with fiʻil has 19 data, isim with isim is 21, the combination of fiʻil and isim has 2 data, and harf with harf have 6 data. While the form of ṭibāq salab which consists of fiʻil with fiʻil has 11 data, isim with isim has 3 data, and the combination of fiʻil and isim has one data.